2021
DOI: 10.52547/jps.20.106.1897
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effectiveness of compassion focused therapy and dialectical behavior therapy on reducing the marital conflict of women on the threshold of the divorce

Abstract: Background: Marital conflict can shake the foundations of cohabitation and provide the ground for an emotional and formal divorce. The effectiveness of dialectical behavioral therapy and compassionfocused therapy has been confirmed on various variables, but there is a research gap in the comparison and impact of these two therapies on marital conflict. Aims: The aim of this study was to Comparison of the effectiveness of CFT and DBT on reducing the marital conflict of women on the threshold of divorce. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
0
0
Order By: Relevance
“…The results of the repeated measures analysis of variance showed that compassion-based spouse-treating education was effective in improving family relationships and forgiveness among deaf men in Isfahan. Although no research has previously examined the effectiveness of compassion-based spouse-treating education on improving family relationships and forgiveness among men to compare the alignment or misalignment with other studies, the findings of this study regarding the effectiveness of this method on other psychological constructs are consistent with the results of other research (Aminifar et al, 2023;Dashtbozorgi, 2018;Dehkordi et al, 2019;Hasani et al, 2021;Peymannia et al, 2018;Ramezani et al, 2023;Rostami et al, 2016;Saadati et al, 2021;Tabibzadeh et al, 2021;Tajdin et al, 2021;Yaghoobi et al, 2021).…”
Section: Discussionsupporting
confidence: 87%
“…The results of the repeated measures analysis of variance showed that compassion-based spouse-treating education was effective in improving family relationships and forgiveness among deaf men in Isfahan. Although no research has previously examined the effectiveness of compassion-based spouse-treating education on improving family relationships and forgiveness among men to compare the alignment or misalignment with other studies, the findings of this study regarding the effectiveness of this method on other psychological constructs are consistent with the results of other research (Aminifar et al, 2023;Dashtbozorgi, 2018;Dehkordi et al, 2019;Hasani et al, 2021;Peymannia et al, 2018;Ramezani et al, 2023;Rostami et al, 2016;Saadati et al, 2021;Tabibzadeh et al, 2021;Tajdin et al, 2021;Yaghoobi et al, 2021).…”
Section: Discussionsupporting
confidence: 87%